FINANCIAL RISK MANAGEMENT IN THE ERA OF ECONOMIC UNCERTAINTY: LESSONS FROM GLOBAL CRISIS - Moridu, Irwan (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Financial Risk Management has experienced significant evolution in the face of economic uncertainty resulting from various global crises, including the 2008 Financial Crisis and the COVID-19 Pandemic. This research aims to analyze how FRM strategies develop over time using a Systematic Literature Review (SLR) approach. Through comprehensive literature analysis, this research identifies patterns of change in risk management approaches, the impact of regulations, and the industrial sector's response to the crisis. The findings show that there is a shift from traditional models based on historical data towards more adaptive technology-based strategies, including the use of AI and Big Data. Additionally, regulations such as Basel III and the Dodd-Frank Act have strengthened the resilience of the financial system. This research provides important insights for practitioners and policy makers in designing more effective risk mitigation strategies in an era of global economic uncertainty.